O sistema de valores humanos de administradores brasileiros: adaptação da escala PVQ para o estudo de valores no Brasil - Almeida, Filipe Jorge Ribeiro de (2009)
The human values of managers and their implications in corporate performance have increasingly became a subject of interest for social scientists all over the world, much due to the recent contributions from psychology which provided reasoning and practical solutions for understanding and studying values. In this context, Schwartz's motivational theory is one of the most representative contributions. This paper aims at studying the human values system of Brazilian managers through the application of a revised version of the PVQ scale originally proposed by Schwartz. Results confirm the validity of this new adapted version of the PVQ for studying higher order values in Brazilian context, although it seems less robust for studying motivational type values. Brazilian managers seem to attribute higher value to individual autonomy as motivator for volunteer cooperation and pursuit of social well-being, valuing freedom and igualitarism over hierarchy and formality in social interactions.